The Humanization of Punishment Through Conditional Death Penalty: Reconstruction of Court Decisions Within the Framework of the National Criminal Code - Eva Dwi Dayati; Rani Hendriana (Jurnal Hukum Samudra Keadilan, 2026)
The National Criminal Code marks a shift in the paradigm of punishment from retributive to restorative. This change is reflected in Decision Number 813 K/Pid/2023, which amended the decision of the Jakarta High Court by imposing a life sentence, indicating a tendency for judges not to uphold the death penalty as the final sanction. This study uses a normative legal method with a legislative and case approach. The focus of the research is to analyze the concept of the death penalty in the National Criminal Code and to formulate a reconstruction of court decisions that integrate the principle of humanity. The results of the study show that the death penalty is no longer absolute, but rather an ultimum remedium that considers the subjective aspects of the perpetrator, and this study offers an update to the norms related to probation, standards for imposing sanctions, and judicial considerations.